Explanation of the Role of Intermediary Perception of Organizational Justice in Relationships between Abusive Supervision and Innovative Self-Efficacy - Rahmatollah Marzooghi; Heidari Elham (Tehran University of Medical Sciences, 2017)
Background and Aim: To fulfill its mission, the health system needs reform in various sectors including supervisory areas. That is because the quality of supervision can have various consequences such as increase or decrease of innovative self-efficacy through various factors. Therefore, the aim of this study was to explain the mediator role of perception of organizational justice in the relationship between abusive supervision and innovative self-efficacy. Materials and Methods: This is a correlational descriptive-analytical study. The sample included 225 employees of Shiraz University of Medical Sciences, who were selected through random sampling. The research instruments were questionnaires of abusive supervision, innovative self-efficacy and perception of organizational justice, which were distributed among the sample after calculating their reliability and validity.  Results: The results showed that abusive supervision had a significant negative impact on the perception of organizational justice and employee's innovative self-efficacy. Also, the perception of distributive justice has a significant positive impact on innovative self-efficacy and a mediation role in the relationship between abusive supervision and innovative self-efficacy. Conclusion: In order to enjoy innovation, health-oriented organizations should reduce abusive supervision in managers' and supervisors' behavior; therefore, with the increase of employees' feeling of innovative self-efficacy, they can lead to the realization of the mission of these organizations.